Characteristics of six new para-fluorophenylalanine resistant loci of Aspergillus nidulans. - B. N. Tiwary; U. Sinha (Fungal Genetics Reports, 1987)
Characteristics of six new para-fluorophenylalanine resistant loci of Aspergillus nidulans.